Implikasi Strategi Pemasaran Produk Halal di Masa Pandemi Covid-19 : Studi Kasus Pada UMKM di Salatiga - sari wijayanti (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2022)
This research is about Marketing Strategy Implication of Halal Product on Covid-19 Pandemic, focus on SMEs in Salatiga.  The aims of this research is to describe why SMEs using halal product as its marketing strategy on Covid-19 Pandemic and how the impact of halal product marketing strategy on Covid-19 Pandemic. This research is using qualitative research, conduct with interview, built pattern, concept and connected them become a mini-theory. The results of this research are: (1) Adding the halal logo as a reflection of halal certification as marketing strategy is applied on covid-19 pandemic, (2) The impact of marketing strategy halal product are sales increase, price increase, packaging change, and production process change. Suggesstion for the next research is examining quantitatively the mini-theory.